Reconceptualizing racism in Khaled Hosseini's The Kite Runner and J. M. Coetzee's Disgrace - Ghimire, Surendra Prasad (Humanities, Arts and Social Sciences Studies, 2024)
This study reports how Khaled Hosseini's The Kite Runner and J. M. Coetzee's Disgrace depict racism in different contexts and how racially victimized people understand and interpret racism based on their diverse racial perceptions and experiences. In this study, Sally Haslanger's notion of racism as a social construction and Ali Rattansi's idea of racism as a social prejudice are utilized as theoretical perspectives to analyze the both novels. The findings reveal that racially victimized people in Hosseini's The Kite Runner conceptualize racism as the social exclusion of minority ethnic groups by depriving them of receiving the essential requirements of their lives, and the findings further identify that racism is interconnected with religion and creates an overarching impact in human relations by creating social division. Moreover, the study uncovers the fact that racially victimized people in Coetzee's Disgrace interpret racism as the exploitation of mainly non-whites and a form of revenge for the white treatment of non-whites in the colonial period. In addition, the study reveals that the realization of racism is based on individual perception and power dynamics in local contexts instead of universally homogenizing perceptions and experiences of victimized people. This study has great significance as it reconceptualizes racism from victimized perspectives and provides a clear direction for further exploration of racism in novels and daily social activities.